Altered brain spontaneous and synchronization activity in latent autoimmune diabetes in adults: A resting‐state functional MRI study. Issue 1 (7th November 2022) - Miao, Yingwen; Wang, Jin; Zhang, Bing; Zhang, Wen; Xu, Xiang; Hou, Yingjiao; Ding, Qun; Yu, Congcong; Zhang, Zhou; Bi, Yan; Zhu, Dalong
Abstract: Aims: This study aimed to explore the clinical features and spontaneous brain activity among patients with latent autoimmune diabetes in adults (LADA) and to investigate the relationship among these characteristics. Methods: We conducted a cross‐sectional study using cognitive assessments and resting‐state functional magnetic resonance imaging (rs‐fMRI) to evaluate the cognitive function and brain activities of healthy controls (HCs) and patients with LADA. Functional connectivity (FC) analysis was performed on the brain regions that showed significantly different activation in regional homogeneity (ReHo) analysis between the two groups. Furthermore, a linear regression model was conducted for the association between metabolism and cognition. Results: This study enrolled patients with LADA (and age‐, sex‐, and education‐matched HCs). Patients with LADA had worse cognitive status at the general level and poorer memory than controls. Rs‐fMRI analysis among patients with LADA showed decreased ReHo values in the right occipital lobe and temporal lobe and decreased seed‐based FC in the right parietal lobe compared to those of controls. The seed‐based FC values in the right parietal lobe were positively associated with word fluency and processing speed in patients with LADA. Furthermore, low‐density lipoprotein cholesterol was negatively correlated with Montreal Cognitive Assessment scores in patients with LADA. Conclusions: Patients with LADA had worse cognitive function and decreased spontaneous brain activity in the temporal lobe and occipital lobe compared to controls. Moreover, glycolipid metabolism was closely related to brain structure and function in patients with LADA.